Evaluasi Sistem Informasi Manajemen Puskesmas Dengan Metode PIECES Di Puskesmas Kemuningsrai Kidul Kabupaten Jember - Dita Tinsi Riani; Gamasiano Alfiansyah; Atma Deharja; Mudafiq Riyan Pratama (Manajemen Pelayanan Kesehatan, 2024)
Kemuningsarı Kıdul Community Health Center has been using SIMPUS as from 2013. The SIMPUS implemented at Kemuningsarı Community Health Center still has several problems that often occur, including reports that are still manual, and SIMPUS is not yet integrated with P-Care. The objective of this study was to assess user satisfaction with SIMPUS at the Kemuningsarı Kıdul Community Health Center by examining information,  performance, economic factors, service quality efficiency, and control using the PIECES framework. Qualitative research methodology was employed in this study, utilizing data collection methods such as observation, interviews, brainstorming, and documentation. The research subjects were one filing officer, registration officer, head of administration, member of administration, Head of community health center and vendor. The resulted of the research obtained information based on the SIMPUS performance aspect have not been running according to user needs and do not have a good response time, the information aspect has not provided information according to user needs, the economic aspect has not been integrated with P-Care, the control aspect SIMPUS has a low level of security, the efficiency aspect of Learning and operating SIMPUS proved to be straightforward and uncomplicated, the service aspect of the information produced cannot be trusted and relied upon. An alternative solution was to update SIMPUS and replace the software and hardware in the medical record unit, and hold training for SIMPUS users for a minimum of 3 months at a time. Researchers provide present for implementing data encryption in SIMPUS at the Kemuningsari Kidul Community Medical Facility.